An Exploratory Study of the Effectiveness of Unconditional EducationalAssistance Program as a Programmatic Electoral Strategy in the Philippines: The Case of Makati City’s Project FREE - Miguel Enrico Gutierrez Ayson; Esther Marylerma Calvo (Jurnal Studi Pemerintahan)
This exploratory study deviated from the influential theoretical lens of clientelism in examining voter-politician ties in Philippine political studies. Drawing on Kitschelt and Wilkinson’s (2007) conceptualization of programmatic politics as an alternative electoral strategy, we investigated how a programmatic linkage between a local political leader and its electoral constituency is facilitated through the non-contingent and regular distribution of school-related materials for public school children. This local programmatic policy has gained popularity among various local government units (LGUs) in the Philippines. We focused on the Makati City government’s Project FREE (Free Relevant and Excellent Education) due to its reputation for arguably being the most innovative and comprehensive educational assistance program ever implemented at the country’s local scale. We employed a purposive sampling technique to obtain our participants – the project’s parent beneficiaries. Through in-depth interviews, we investigated the attitudes and perceptions of Project FREE’s parent beneficiaries towards the mayor’s programmatic commitment to them. By using thematic analysis, five themes emerged from the interview data: (1) financial relief, (2) educational security, (3) unique source of local citizen satisfaction, (4) personally dispensed patronage of a benefactor politician, and (5) invaluable benefits and project continuity: influencing vote preference. Beyond the particularistic and contingency-based patronage exchange prevalent in the Philippine local political setting, this study’s findings also offer in-depth explanations for what motivates voters to reciprocate their local political leader with electoral support for its education-based programmatic inducements.